Pemikiran Sayyid Ja’far Al-Barzanji: Pengaruhnya Terhadap Tradisi Keagamaan Dan Budaya Islam Di Indonesia - Baits, Abdul (Mazalat: Jurnal Pemikiran Islam, 2024)
This article aims to analyse the thoughts of Sayyid Ja'far Al-Barzanji and his influence on religious traditions and Islamic culture in Indonesia. The main focus of this research is to examine the work of Maulid Al-Barzanji, which has become an important intellectual and spiritual heritage in the Islamic world, especially in Indonesia. This research uses a literary approach by examining primary sources in the form of Maulid Al-Barzanji's texts and secondary literature related to Islamic history, culture and theology. The results show that Al-Barzanji's thought has had a significant impact on the formation of religious traditions in Indonesia, particularly through the celebration of the Prophet's Maulid, which has been adapted into various local rituals. In addition, the recitation of Maulid Al-Barzanji has become a medium for strengthening people's solidarity, teaching spiritual values and expressing Islamic art. For example, in some regions, such as Java and Sumatra, the recitation of the Barzanji is not only part of religious celebrations, but also of traditional ceremonies such as weddings and births. This tradition shows a unique integration between local culture and Islam, reflecting the beauty of cultural and religious harmony in Indonesia.